From Fatwa to Law: Epistemic Authority and Hybrid Legal Legitimacy in Islamic Financial Regulation - Zukhrufin; Mita Alisah Tazkiyah; Saifudin (FEBI IAIN Langsa, 2026)
This study examines how fatwa acquires legal authority in Islamic financial regulation within pluralistic legal systems. Using a PRISMA-based systematic literature review and reflexive thematic analysis, it analyzes the transformation of fatwa into formal regulatory frameworks. Drawing on legal pluralism and legal legitimacy theories, the study argues that Islamic financial regulation operates within a hybrid legal structure where state law, Sharia principles, and global standards interact dynamically. The findings identify a dominant pattern in the literature: fatwa consistently functions as an epistemic authority, institutionalized through Sharia governance mechanisms and translated into binding regulatory norms. Through processes of interpretation, institutional mediation, and regulatory codification, fatwa evolves from a non-binding religious opinion into legally recognized norms, conceptualized here as an epistemic-legal transformation. This transformation is mediated by governance structures that bridge religious knowledge and formal legal systems. The study further demonstrates that legal legitimacy in Islamic finance is a hybrid construct integrating formal, social, and epistemic dimensions. By advancing the concept of hybrid legal legitimacy and the framework of epistemic-legal transformation, this study contributes to legal theory by incorporating epistemic authority into the analysis of law in pluralistic systems. Practically, the findings suggest that policymakers and regulators should strengthen institutional mechanisms that integrate fatwa into formal regulation to enhance legal certainty, consistency, and public trust in Islamic financial systems.